Determinants of Loan Access towards Financial Performance in MSMEs - Syti Sarah Maesaroh (ADI Publisher, 2021)
Low competitiveness is one of the obstacles to improving the performance of MSMEs. One of the factors that cause this is the lack of access for MSMEs to financial institution facilities. This study aims to analyze the financial performance of MSMEs seen from the accessibility factor to financial facilities provided by various financial institutions in Tasikmalaya City. The study used a quantitative descriptive method. Data analysis used the PLS Structural Equation Model (PLS-SEM). The sample consisted of 100 SMEs in the creative economy sub-sector through the random sampling method. The analysis technique uses a path analysis model to see the causal relationship between variables, either directly or indirectly. Data were obtained through direct interviews with SMEs using closed questionnaires. The results show that management administration has a direct or indirect effect on financial performance. The management of administration is important to improve accessibility to the financial performance of MSMEs. Guidance for MSMEs is needed to ensure that loans can be utilized optimally for business development.